Tingkat Kepuasan Pelayanan Swamedikasi Batuk di Toko Obat Arjasari - Fikriyyah, Fikriyyah; Adriansyah, Rizky (Publikasi Indonesia, 2022)
Cough is a common complaint encountered by the community and is classified as mild. Therefore, people prefer to self-medicate when faced with it. However, in practice, self-medication can be a source of medication errors due to limited public knowledge about drugs and their use. Provide a good understanding to the community about cough self-medication from a pharmacist. The purpose of this study was to determine how satisfied the cough self-medication service was at the Arjasari pharmacy. This type of research uses a qualitative design with descriptive research methods. Collecting data, namely all data that meet the inclusion and exclusion criteria. From the research, the results of the sperman rank correlation coefficient of (0.806) indicate that the variables of reliability, responsiveness, assurance, empathy, and tangibles together or simultaneously have a significant effect on customer satisfaction (64.9%), while the remaining variables (35 ,1%) contributed by other variables not examined by the authors. Based on the research that I have done, based on the results of the study it can be concluded that the majority of customers are very satisfied with service performance in terms of service quality perceived by customers. Arjasari drug store clerk in serving self-medication customers.